A high performance UV–visible dual-band photodetector based on an inorganic Cs2SnI6 perovskite/ZnO heterojunction structure. Issue 5 (3rd January 2020) - Shao, Dali; Zhu, Weiguang; Xin, Guoqing; Liu, Xueqing; Wang, Tianmeng; Shi, Sufei; Lian, Jie; Sawyer, Shayla
Abstract : Inorganic perovskite/ZnO heterojunction photodetector with UV-visible dual-band detection capability. Abstract : Inorganic metal halide (IMH) perovskites have recently emerged as highly promising optoelectronic materials due to their excellent material properties, including tunable direct bandgap, long carrier diffusion length, high carrier mobility and outstanding environmental stabilities. However, the performance of photodetectors fabricated from IMH perovskites so far is limited as compared to their counterparts based on organic–inorganic hybrid perovskites. In this work, we demonstrate a high performance ultraviolet–visible (UV–Vis) dual-band photodetector based on a Cs2 SnI6 /ZnO heterojunction structure. By adjusting the polarity of the applied bias voltage, the photodetector can switch between two operation modes: (1) UV–Vis dual-band detection mode and (2) visible-blind UV detection mode. High detectivity in both the UV (1.39 × 10 12 Jones) and visible (5.88 × 10 11 Jones) regions is achieved. In addition, this photodetector demonstrated a fast response speed with a rise and fall time on the order of milliseconds and a large linear dynamic range of 119 dB. The excellent performance of this photodetector originates from efficient charge separation at the heterojunction interfaces, which will be discussed in detail in terms of the energy band diagrams and carrier dynamics of the device. Our study demonstrates the great application potential of inorganic vacancy-ordered perovskites in high-performance heterojunction photodetectors.